Remote Origins: The case of 'Water Towns', of Olbicella, and of root *alb- - Perono Cacciafoco, Francesco (2016)
Palaeo-Ligurian place-names of the type Alba, Old European river names Albis and the like, as well as their ablauting forms Olb- (> Orb- in Romance Ligurian) do not reflect directly Proto-Indo-European adjective *albho-‘white’; rather, they all continue a Pre-PIE extended root *Hal-bh- ‘water’cognate with Sumerian halbia (> Akkadian halpium ‘well, water mass, waterhole’). A further analysis of *Hal-bh- leads to a comparison with PIE root*Hal- ‘nourish’. PIE suffixed form *HwaH-r- ‘water’ exhibits a similar diffusion.